Collaborative learning for the improvement of writing skills to first baccalaureate students level A2 at unidad educativa Eugenio Espejo, school year 2021-2022 - Serrano Jama, Washington Michael (2022)
Writing is an important element of our real interactions. But learning and performing is a challenging task, Professionals may assist the learners enhance their writing skills at a younger year by starting some easy exercises. It will contribute as a learner and as a teacher to their future achievement, while teaching them what they want to say. Each person must write every day, whether they complete a form in any field, or compose an essential letter to accomplish their duties. These duties need us to be clear and efficient in the organization of information. Either students write by hand or on their desktop, many courses and examinations require students to produce brief responses or lengthier essays in order to evaluate what they have learned. As learners become older, more advanced abilities in writing should be developed and complicated tasks completed through writing them. Furthermore, if you wish to study abroad, many universities and schools ask you to submit essays as part of your application for admission. This is why an additional book with didactic strategies for developing this English skill which is regarded as one of the most important in this foreign language is important.